Analysis of nursing staff job satisfaction and its influencing factors: a cross-sectional study of 38 hospitals/nursing homes in China - Zhao, Yu; Lu, Hui-Qun; Xu, Yun; Lu, Jie-Yu (Frontiers in Public Health, 2025)
BackgroundNurses’ job satisfaction directly impacts their attitudes and efficiency at work. This study aimed to identify the factors influencing job satisfaction among nursing professionals in China.MethodsThis cross-sectional study utilized an online questionnaire to assess the job satisfaction, work conditions, and sociodemographic characteristics of nursing professionals in China. Data were analyzed using descriptive statistics, chi-square tests, Spearman correlation analysis, and linear regression analysis.ResultsThe study collected 605 questionnaires from 38 hospitals and nursing homes in Nantong. Among them, 599 were valid responses, resulting in a validity rate of 99%. The majority of participants were aged 51–60 (43.14%) and were female (91.65%). The multivariate model results indicated that age, work location, and policy understanding significantly influenced overall job satisfaction. Specifically, the 51–60 age group and those aged ≥61 had a positive impact on overall satisfaction compared to the ≤30 age group (β = 0.95, 95% CI = 0.43 to 1.47; β = 1.53, 95% CI = 0.82 to 2.25). Compared to working in a hospital, working in a nursing home had a negative impact (β = −1.13, 95%CI = −2.10 to −0.17). Additionally, lower policy understanding negatively affected overall job satisfaction.ConclusionThis study found that age, workplace, and policy understanding are factors influencing the job satisfaction of nursing staff. Therefore, corresponding measures should be taken for young nurses and those working in nursing homes, such as improving welfare benefits and reducing work pressure, to enhance their job satisfaction. In addition, training for all nursing staff should be strengthened to improve their understanding of relevant policies, thereby increasing job satisfaction and retention rates. This will help better meet the growing demand for nursing services.